Transformation of family structure and system of values: case analysis of casuistic compulsion - Кочарян, А. С.; Баринова, Н. В. (Psychological Counseling and Psychotherapy, 2017)
The article presents a rare case of obsessive behavior of the client, consisting in a daily manual cleaning of the rectum before going to work. The pathogenesis of this disorder, the psychosemantic structure of relationships in the client's family, the connotative structure of its core values and the psychosemantic structure of the client's I-existence are considered. A number of psychosemantic distortions are revealed: 1) destruction of denotative and connotative structures of images of "spouse" and "child"; 2) the destruction of the value-motivational sphere, which is manifested by the phenomena of "value emptiness", "anhedonism" and "value incongruence"; 3) ego-dystonia of important spheres of personal functioning